Concentration of vitamin D metabolite - 25(OH)D3 as a predictor of breast cancer progression - D. Е. Frolova; N. P. Lapochkina; О. А. Gromova; I. Yu. Torshin (IRBIS LLC, 2023)
Background. Prediction of breast cancer (BC) progression is important for the timely correction of patient therapy.Objective: to assess a relationship between BC progression and degree of vitamin D deficiency.Material and methods. A retrospective controlled study was performed. The results of examining 67 women aged 29-48 years with histologically verified BC and vitamin D deficiency are presented. All patients were divided into two groups: the main group - 34 women administered with vitamin D, comparison group - 33 patients not taking vitamin D.Results. It was shown that 25(OH)D3 level less than 18.9 ng/ml was significantly associated with prominent disease progression, regardless of the tumor molecular subtype. Additional criteria were developed allowing to predict BC progression.Conclusion. In order to detect secondary changes (distant metastases in ВС patients) and improve patient monitoring, it is recommended to use additional diagnostic methods and determine the intermediate metabolite of vitamin D - 25(OH)D3 in peripheral blood.